Enhancing the passive design of buildings: A mixed integer non-linear programming approach for the selection of building materials and construction building systems - Hammad, Ahmed W.A.; Figueiredo, Karoline; Rosa, Ana Carolina; Vazquez, Elaine; Haddad, Assed (Energy reports, 2021)
Consumption of energy in buildings accounts for a considerable proportion of worldwide energy use. There is a dire need for enhancing the energy efficiency of building to limit their demand for operating energy as this leads to enhanced reductions in environmental impacts. Of particular relevance to the amount of energy utilised in a building during the operation phase is the nature of material and size of components utilised in the building. In this work, a mathematical programming framework is presented to optimise a number of building design objective functions, including heat gain, daylight and economic cost of material utilised. The variables that are focussed on in this study are the sizes of windows, type of material adopted for the building, embodied in the construction building systems used for various building components, and the type of lighting adopted. To validate the framework, two realistic case studies obtained from an industry partner are adopted and solved via the use of the proposed mathematical programming method. Results indicate that compared to the solutions proposed by an experienced engineer, the daylight, heating and cost of the building is enhanced by up to 39%, 43% and 23% respectively. The framework is hoped to help policy makers introduce more streamlined guidance for the building sector when it comes to optimised material choice and window sizing to result in energy-efficient and economical buildings. [Display omitted] •A framework is presented to optimise some building design objective functions.•Two realistic case studies are adopted and solved using the proposed framework.•The mathematical programming includes heat gain, daylight, and material cost.•The variables are focused on window sizes, type of building materials and lighting.•The framework is hoped to introduce more streamlined guidance for the building sector.